Estudo de caso sobre o processo de redesign e gamificação do sistema de levantamento de necessidades de capacitação da Pró- Reitoria de Gestão de Pessoas (UFRN) - Veras, Ruth Praxedes de Paiva (2017)
The Federal University of Rio Grande do Norte – UFRN, has its own softwares developed by the institution and has been concerned about solving problems related to user's interaction difficulties in these softwares, which are misunderstanding about how to operate the software, incompatible language with the user’s daily routine, among others. Furthermore, there are reports about lack of interest from the users in performing some tasks on the software because they are considered tiresome and/or uninteresting. In order to solve these problems, the UFRN, through the PROGESP – people management department, developed the Gamification Project in the middle of 2015 / early 2016. The Gamification has occurred on some functions in the human resources software – SIGRH, among those, the Training Needs Survey – LNC who has gained a new interface with game elements. The Gamification Project followed the guidelines from the User Centred Design – UCD, which is an approach of products development. This paper is a study case that sought to investigate the LNC gamification process, verifying the characteristics adopted from UCD guidelines and which game elements have been used in the Gamification, analyzing how Gamification and UCD can influence the results obtained by the project. Furthermore, it was sought to evaluate the software with a group of users, using the Cooperative Evaluation and questionnaire technics, analyzing the user’s perception about the software’s changes and identifying whether there could be some aspects to improve at LNC. The research showed that the major part of the users has approved the change and that Gamification and UCD have contributed to this positive result, but also revealed several aspects to be improved, so the tool can attend properly all the users and their needs.